2010
DOI: 10.1177/1012690209356988
|View full text |Cite
|
Sign up to set email alerts
|

(Re)engaging marginalized groups through sport: The Homeless World Cup

Abstract: Marginalized groups, such as those experiencing homelessness, are largely excluded from participation in, and the benefits provided by, sport programs and events. This study uses the case of the 'Street Socceroos', the Australian Homeless World Cup team, to argue that participation in sport can provide beneficial outcomes for participants, and through a process of (re)engagement, develop social capital. Drawing on interviews and observations with team members before and after the Homeless World Cup, this study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
90
0
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 108 publications
(112 citation statements)
references
References 31 publications
3
90
0
4
Order By: Relevance
“…Many of these stem from a wider social studies or community development context; interestingly, the two frameworks most often used are positive youth development (e.g., Agans & Geldhof, 2012;Holt, Sehn, Spence, Newton & Ball, 2012) and social capital theory (e.g., Schulenkorf, Thomson, & Schlenker, 2011;Sherry, 2010). The latter has often been praised as highly productive and "successful"; however, it has also been criticized as an ambiguous "last resort" for studies that do not seem to find or apply any better framework.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…Many of these stem from a wider social studies or community development context; interestingly, the two frameworks most often used are positive youth development (e.g., Agans & Geldhof, 2012;Holt, Sehn, Spence, Newton & Ball, 2012) and social capital theory (e.g., Schulenkorf, Thomson, & Schlenker, 2011;Sherry, 2010). The latter has often been praised as highly productive and "successful"; however, it has also been criticized as an ambiguous "last resort" for studies that do not seem to find or apply any better framework.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…A significant focus has been placed on initiatives aimed at creating social cohesion (e.g., Sherry, 2010) and providing opportunities for education (e.g., Burnett, 2010), often for members of disadvantaged communities (e.g., Sherry & Strybosch, 2012;Welty-Peachy, Cohen, Borland & Lyras, 2013). However, our findings also revealed that to establish a strong evidence base for SFD, more research is needed particularly in the areas of disability, gender equality, and livelihoods.…”
Section: Thematic Areasmentioning
confidence: 99%
“…Several studies have explored the contribution of sports events in shaping social identities and intercultural relations, overcoming social boundaries, downplaying interpersonal and intergroup discriminations. Such events have been analysed for their potential to influence national and ethnic belonging (Dallaire & Denis, 2005), integrate marginalised groups (Krowel, Boonstra, Duyvendak, & Veldboer, 2006;Sherry, 2010), promote gender equality (Elling, De Knop, & Knoppers, 2003), and reconcile divided communities (Gasser & Levinsen, 2004;Schulenkorf, 2010;Sorek, 2003;Sterchele, 2007;Sugden, 2006).…”
mentioning
confidence: 99%
“…Besides providing enthusiasm and enjoyment, the striving for a goal and the desire for achievement nurtured by the competitive dimension of sports activities can also play an important role in motivating individuals and groups to recover from different conditions of social isolation re-awakening active and positive attitudes (Carless, Peacock, McKenna & Cooke, 2013;Richards, 1997;Sherry, 2010).…”
Section: Resultsmentioning
confidence: 99%